Trained innate immunity, epigenetics, and food allergy - Llilian Arzola-Martínez; Llilian Arzola-Martínez; Catherine Ptaschinski; Catherine Ptaschinski; Nicholas W. Lukacs; Nicholas W. Lukacs (Frontiers in Allergy, 2023)
In recent years the increased incidence of food allergy in Western culture has been associated with environmental factors and an inappropriate immune phenotype. While the adaptive immune changes in food allergy development and progression have been well-characterized, an increase in innate cell frequency and activation status has also recently received greater attention. Early in prenatal and neonatal development of human immunity there is a reliance on epigenetic and metabolic changes that stem from environmental factors, which are critical in training the immune outcomes. In the present review, we discuss how trained immunity is regulated by epigenetic, microbial and metabolic factors, and how these factors and their impact on innate immunity have been linked to the development of food allergy. We further summarize current efforts to use probiotics as a potential therapeutic approach to reverse the epigenetic and metabolic signatures and prevent the development of severe anaphylactic food allergy, as well as the potential use of trained immunity as a diagnostic and management strategy. Finally, trained immunity is presented as one of the mechanisms of action of allergen-specific immunotherapy to promote tolerogenic responses in allergic individuals.